The complex interplay between right ventricular dysfunction and atrial fibrillation - a narrative review - Vijan Ancuta; Daha Ioana Cristina; Delcea Caterina; Dan Gheorghe-Andrei (Sciendo, 2023)
Atrial fibrillation (AF) is one of the most common sustained arrhythmias in clinical practice, associated with multiple comorbidities and complication. The potential predictors of AF onset and perpetuation or specific drivers of complications need future investigation. Right ventricular (RV) dysfunction plays an important role in the development of new-onset AF warranting in-depth analysis in relation to AF. RV may play a significant role in a better characterization of the cardiac substrate of AF patients. The relation between RV dysfunction and AF is bidirectional as AF may be one of the causes of RV dysfunction and their coexistence worsens the overall patient prognosis. Our aim is to present in a narrative review the most relevant data regarding the complex relationship between AF and RV dysfunction.